RETRACTED: Allelotyping PCR for Detection and Screening of Salmonella enterica Serovar Enteritidis and Typhimurium - Soliman, S. Essam; Kilpatrick, C.; Ahmed, S. Mohamed; Abouelhassan, M. Eman; Nimmanapelli, R.; Reddy, P.G. (International Journal of Poultry Science, 2009)
A CASE OF PLAGIARISM (Case No. 05012013) Professor John J. Maurer from The University of Georgia 244, 5th Avenue, No. 2218 NY 10001, New York USA pointed out a plagiarism in a paper published in International Journal of Poultry Science Volume 8 Number 2, 156-160, 2009. On the receipt of Professor John J. Maurer’s letter, the case forwarded to the Ethics Committee of the International Journal of Poultry Science. As per the report of the Ethics Committee, article entitled "Allelotyping PCR for Detection and Screening of Salmonella enterica Serovar Enteritidis and Typhimurium" authored by S. Essam Soliman, C. Kilpatrick, S. Mohamed Ahmed, M. Eman Abouelhassan, R. Nimmanapelli and P.G. Reddy Department of Pathobiology, CVMNAH, Tuskegee University, USA published in International Journal of Poultry Science Volume 8 Number 2, 156-160, 2009, contains substantial sections of text that have been taken verbatim from earlier publication without clear and unambiguous attribution. International Journal of Poultry Science considers misappropriation of intellectual property and duplication of text from other authors or publications without clear and unambiguous attribution totally unacceptable. Plagiarism is a violation of copyright and a serious breach of scientific ethics. The Editors and Publisher have agreed to officially retract this article. International Journal of Poultry Science is highly thankful to Professor John J. Maurer The University of Georgia 244, 5th Avenue, No. 2218 NY 10001, New York USA, for pointing out this plagiarism. Detail of article from which text has been copied by S. Essam Soliman, C. Kilpatrick, S. Mohamed Ahmed, M. Eman Abouelhassan, R. Nimmanapelli and P.G. Reddy: Yang Hong, Tongrui Liu, Margie D Lee, Charles L Hofacre, Marie Maier, David G White, Sherry Ayers, Lihua Wang, Roy Berghaus, John J Maurer, 2008. Rapid screening of Salmonella enterica serovars Enteritidis, Hadar, Heidelberg and Typhimurium using a serologically-correlative allelotyping PCR targeting the O and H antigen alleles from BMC Microbiology, 8: 178, 2008. Doi: 10.1186/1471-2180-8-178